Warehousing takes off - Connolly, James (Computerworld, 1997)
Industry experts say that object databases are overhyped and that the biggest trends in 1997 will be the use of data warehousing, data mining, and Web-enabled databases. Scalability and Internet connectivity are the major areas where progress is being made, according to Performance Computing INc president Richard Finkelstein. Research analyst Morgan Gerhart says that data warehouses in general and single-subject data marts in particular will draw the most attention in the near future. International Data Corp researcher Carl Olofson warns that different vendors will approach data warehousing differently. Vendors will continue to add support for more powerful SMP and parallel-processing systems as the move to data warehouses demands better performance. Data warehouses place heavy I/O demands on a system; some vendors are trying to speed the process, while others work to reduce I/O needs in general.